Dodonaea viscosa Jacq. induces cytotoxicity, antiproliferative activity, and cell death in colorectal cancer cells via regulation of caspase 3 and p53 - Herrera-Calderon, Oscar; Herrera-Ramírez, Angie; Cardona-G, Wilson; Melgar-Merino, Elizabeth Julia; Chávez, Haydee; Pari-Olarte, Josefa Bertha; Loyola-Gonzales, Eddie; Kong-Chirinos, José Francisco; Almeida-Galindo, José Santiago; Peña-Rojas, Gilmar; Andía-Ayme, Vidalina (Frontiers in Pharmacology, 2023)
Colorectal cancer (CRC) is often diagnosed in extremely advanced stages and because of this, mortality rates are sig-nificantly high. Due to those high death rates and the insufficiency prognosis, there is an urgent need to investigate new alternatives that could potentially be used to combat any of the stages of this such deadly disease. Thus, Dodonaea viscosa, a Peruvian medicinal herb known to treat inflammatory conditions, has been explored because of its wide range of biological activities against different diseases. The purpose of this study was to examine the cytotoxic, antiproliferative, and cell death-inducing effects of D. viscosa Jacq on colorectal cancer cells. The hydroethanolic extract was carried out by maceration, and its active metabolites were identified using UPLC-ESI-MS. The extract of D. viscosa revealed 57 com-ponents, among which isorhamnetin, kaempferol, quercetin, methyl dodovisate B, hardwickiic acid, viscosol, and dodonic acid were identified. Additionally, the D. viscosa extract induced cytotoxic and antiproliferative activity in both SW480 and SW620 cancer cells, accompanied with, together with important changes in mitochondrial membrane po-tential, formation of the Sub G0/G1 population and increasing levels of apoptotic biomarkers (caspase 3 and the tumor suppressor protein p53) in the metastatic derivative cell line (SW620), suggesting an intrinsic apoptotic process after the treatment with the hydroethanolic extract of D. viscosa.